Home-Range Characteristics and Habitat Use by American Martens in Eastern Newfoundland - Gosse, John W.; Cox, Rodney; Avery, Shawn W. (Oxford University Press, 2005)
We assessed annual home-range area for 23 adult, resident American martens ( Martes americana atrata ) in a low-density population in eastern Newfoundland, Canada (1996–2003), and evaluated seasonal habitat requirements during a peak in abundance of snowshoe hares ( Lepus americanus ). Home-range estimates were 29.54 km2 and 15.19 km2 for males and females, respectively, and reflect significantly larger territories than those maintained by martens across most of their geographic range. We suggest that these exceptionally large territories reflect the low diversity and abundance of small mammals available to martens as prey. Seasonal requirements were examined by using an index to home-range area. The relationship between the index and snowshoe hare abundance indicated that movement rates of individuals decreased during winters when snowshoe hares were abundant, but that this relationship was not apparent during summer. Analyses of stand-scale habitat use indicated that mature coniferous forest was the dominant cover type in most home ranges (49.6% of area) and was the only forest type used proportionately more than its availability by resident martens. Other forest types used in proportion to their availability included coniferous scrub and insect-defoliated stands. Open areas and sites recently disturbed by fire were avoided at this scale.